Using TouchMath to Teach Money Identification to Students with Autism Spectrum Disorders: A Brief Report. (16th April 2023) - Park, Jiyoon; Bassette, Laura; Bouck, Emily
ABSTRACT: Money skills are important for students with autism spectrum disorder (ASD) to successfully live independently. A crucial first step is teaching them money identification. The purpose of this study was to examine the efficacy of using TouchMath money (TMM) to teach middle school students with ASD to count money. A multiple probe design across participants was used to evaluate students' accuracy in solving money identification problems. Results of the study demonstrated that two students showed intervention effects. Yet, the students struggled to generalise the skill. The third student demonstrated varied intervention effects, but the intervention was ended due to his challenging behaviour and end of the school year. Limitations and future directions were also discussed.